Deep gray matter involvement in children with acute disseminated encephalomyelitis. - Baum, P A; Barkovich, A J; Koch, T K; Berg, B O (American Journal of Neuroradiology, 1994)
PURPOSE To review the frequency, distribution, and extent of deep gray matter disease in children with acute disseminated encephalomyelitis. METHODS The MR examinations of 10 patients, who were discharged with the clinical diagnosis of acute disseminated encephalomyelitis between 1986 and 1992, were retrospectively reviewed. Locations of abnormal signal in the cerebral and cerebellar cortices, white matter, and deep gray matter nuclei were recorded. Precontrast and postcontrast images were compared, when available, to assess degree of enhancement (if any). RESULTS Six patients had foci of prolonged T2 relaxation in the deep gray matter, ranging in size from less than 1 cm to 4 cm. The caudate heads were involved in 4 patients, caudate body in 3, globus pallidus in 3, putamina in 3, and thalami in 4. In 1 patient, the thalami were involved nearly symmetrically, with mild mass effect. Asymmetric subcortical white matter involvement was present as well. Prolonged T2 relaxation was present within the cerebral cortex in 4 patients and was associated with subcortical white matter abnormality in 3 and more central white matter disease in 1. Nine of 10 patients demonstrated foci of T2 prolongation in white matter, most commonly involving the subcortical region, corona radiata, and centrum semiovale. Three patients also had periventricular foci. Of the 3 patients receiving gadolinium, one showed no enhancement. Two of the patients showed enhancement of some but not all lesions. One patient, who had normal brain MR findings and symptoms of myelopathy, underwent spine MR which demonstrated focal linear areas of T2 prolongation in the spinal cord at levels C-1 to C-2 and T-6. CONCLUSION Involvement of deep gray matter was common in our small series. The finding of T2 prolongation in these structures does not preclude the diagnosis of acute disseminated encephalomyelitis in the proper clinical setting. Because thalamic involvement is reported to be rare in multiple sclerosis, it may prove useful in distinguishing between acute disseminated encephalomyelitis and the initial presentation of multiple sclerosis.